A Rare Case of Immunotactoid Glomerulopathy Associated with Hodgkin Lymphoma - Keiki Nagaharu; Yuka Sugimoto; Keiki Kawakami (Case Reports in Nephrology)
Immunotactoid glomerulopathy (ITG) is characterized by Congo red-negative microtubular deposits, and it has been reported as a rare paraneoplastic syndrome due to hematologic malignancies, viral infections, or autoimmune diseases. In hematologic malignancies, multiple myeloma and other mature B-cell malignancies are the most common hematologic malignancies, and Hodgkin lymphoma (HL) is extremely rare. A 59-year-old woman was admitted to our hospital because of a pulmonary mass and proteinuria. Computed tomography-guided lung biopsy confirmed the presence of HL stage IIA. Immunofixation of peripheral blood was positive for immunoglobulin G (IgG) kappa. Renal biopsy showed mesangial proliferation with deposits in the subendothelial lesion and no invasion of the HL. These deposits were positive for IgG3, C3, and kappa light chain but negative for C1q and lambda light chain. Electron microscopy showed randomly aligned tubular structures with a diameter of approximately 50 nm. We diagnosed the patient with immunotactoid nephropathy and HL. After systemic chemotherapy, the patient achieved a complete response and loss of proteinuria. On the contrary, her serum monoclonal gammopathy was observed after chemotherapy. The existence of a monoclonal antibody itself might not be a sufficient factor for ITG in some cases, and an additive trigger is necessary for development.